Modelling ice characteristics in iceberg-ship collision analyses - Ferrari N; Rizzuto E; Prestileo A (CRC Press/Balkema, 2015)
The growth of commercial activities in the Arctic region, in particular of LNG transport, due to the recent discovery of new gas fields, brought to the development of new researches in the area of ice loads for ship structures. To consider possible collisions with ice during a design phase, simulations are often real-ized by modelling icebergs as rigid, i.e. non deformable bodies. Results obtained this way may turn out to be too conservative as the ship structure needs to be designed in order to absorb the entire amount of the impact energy. This paper describes an attempt of getting more realistic results by carrying out a collision analysis where both ice and ship are modelled as deformable. A material model describing the mechanical properties of ice is implemented in FORTRAN, for use during finite element analyses of the impact (performed using the software Abaqus CAE). The mathematical model describing ice behaviour is selected among different models present in literature. The ice model is applied in a first case to a specific situation considering a spherical iceberg of given radius impacting the side of a specific ship. The problem is decoupled, following the NORSOK method, into the analysis of a deformable iceberg impacting a rigid ship side and the analysis of the ‘mirror’ situation (rigid iceberg against a deformable ship). For the latter case, reference is made to re-sults available in literature. Outputs from the two analyses are coupled, assuming that the results, separately derived, can be jointly applied to the real case of an impact between two deformable bodies. The results ob-tained in this first application confirm that a significant part of the impact energy is actually dissipated by ice deformation, but they are still valid under the simplifying hypothesis of neglecting the contact interactions be-tween the two deformable bodies. The implemented material model is however ready for being integrated in the FEM analysis to study the coupled problem.